The afterlives of extraction : alternatives and sustainable futures - Calvão, Filipe; Archer, Matthew; Benya, Asanda (International development policy (Brill) ;, 2024)
"The frontiers of extraction are expanding rapidly, driven by a growing demand for minerals and metals that is often motivated by sustainability considerations. Two volumes of International Development Policy are dedicated to the paradoxes and futures of green extractivism, with analyses of experiences from five continents. In this, the second of the two volumes, the 22 authors, using different conceptual approaches and in different empirical contexts, demonstrate the alarming obduracy of the logic of extractivism, even - and perhaps especially - in the growing support for the so-called green transition. The authors highlight the complex and enduring legacies of resource extraction and the urgent need to move beyond extractive models of development towards alternative pathways that prioritise social justice, environmental sustainability, democratic governance and the well-being of both humans and non-humans. They also caution us against the assumption that anti-extraction is anti-extractivist, that post-extraction is post-extractivism, and they critically attune us to the systemic nature of extractivism in ways that both connect and transcend any particular site or scale. This volume accompanies IDP 15, The Lives of Extraction: Identities, Communities, and the Politics of Place"--